THE IMPACT OF ERROR CORRECTION TECHNIQUES ON LEARNER CONFIDENCE AND MOTIVATION - Abdujabborova Dilafroʻz Abdumajid qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Error correction is a central aspect of language teaching and learning, yet its influence on learners’ confidence and motivation remains complex. This study explores how different error correction techniques such as immediate versus delayed feedback and direct versus indirect correction shape learners’ attitudes, willingness to speak, and long-term engagement in the classroom. Data were collected through surveys and interviews with language learners, focusing on their emotional and motivational responses to various forms of feedback. Findings suggest that while some students value immediate and direct correction for its clarity and usefulness, others find it discouraging and prefer delayed or indirect methods that allow for reflection and self-correction. The results highlight the importance of adapting error correction strategies to individual learner preferences in order to foster both confidence and motivation in language learning.